The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.2106/jbjs.cc.20.00809
|View full text |Cite
|
Sign up to set email alerts
|

Diaphyseal Both-Bone Forearm Fracture Due to a Grip Lock Injury in a Female Pediatric Gymnast

Abstract: Case: A 13-year-old female gymnast sustained a diaphyseal both-bone forearm fracture due to a grip lock injury. Conclusion: This is a report of a diaphyseal both-bone forearm fracture due to a grip lock injury in a female pediatric gymnast, successfully treated with closed reduction and cast immobilization. The rare mechanism of injury, education, and treatment have been discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In the literature, as far as we know, a single case study ( n = 1) was identified for DG injury in female gymnasts. According to this case study, which is presented in the current study, Colon et al [ 21 ] reported that a 13-year-old female pediatric gymnast suffered a diaphyseal fracture of both bones in her forearm as a result of a GL injury. Additionally, they reported that the injury was treated successfully with closed reduction and cast immobilization.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…In the literature, as far as we know, a single case study ( n = 1) was identified for DG injury in female gymnasts. According to this case study, which is presented in the current study, Colon et al [ 21 ] reported that a 13-year-old female pediatric gymnast suffered a diaphyseal fracture of both bones in her forearm as a result of a GL injury. Additionally, they reported that the injury was treated successfully with closed reduction and cast immobilization.…”
Section: Discussionmentioning
confidence: 80%
“…The characteristics of the studies included in the systematic review can be found in Table 3 . From the total number of ninety studies, five [ 13 , 18 , 20 , 21 , 34 ] that focused on GL injury were used for this review ( Table 3 ). In contrast, other articles analyzed musculoskeletal issues, fractures of the distal radius, physical injuries in general, mechanisms of upper extremity injuries, muscle activity and its relation to chronic injury, and the impact of sport specialization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations